Afterword - John T. McGreevy (Journal of Moral Theology, 2024)
In 1941, Jacques Maritain mused about writing a variation on the Federalist papers, this time keyed not only to approval of the United States constitution but for the “entire world.” We could use such a document now, as democracies falter. Maritain, more than any other thinker, laid the groundwork for the Catholic Church’s endorsement of democracy. The task today, therefore, is to remember and also improve upon what Maritain once taught us.